Evaluation of the Antibiofilm Activity of Selenium nanoparticles Coated Gutta-Percha: An InVitro Study - G, Manobharathi; Raghu, Sandhya (Journal of Neonatal Surgery, 2025)
Aim: The aim of this study was to enhance the antibiofilm effectiveness of conventional Gutta percha(GP) by modifying its surface with selenium nanoparticles(SeNPs). Materials And Methods: SeNPs were synthesized by a chemical reduction method and used to coat sterilized GP cones through 24-hour immersion for uniform deposition. This in vitro study evaluated and compared the antibiofilm efficacy of selenium nanoparticle-coated gutta-percha (Group 1) and uncoated gutta-percha (Group 2) against Enterococcus faecalis (ATCC 29212) and Staphylococcus aureus (ATCC 25923). Standardized gutta-percha segments were tested using a 96-well microtiter plate model with biofilm formation induced in BHI broth supplemented with 1% glucose. After 24-hour incubation, dislodged biofilms were serially diluted and plated on Mueller-Hinton agar for CFU quantification. Group 1 showed a significant reduction in CFU counts compared to Group 2, indicating enhanced antibiofilm activity. Results: The antibiofilm activity of selenium nanoparticle-coated gutta-percha (C-GP) was evaluated against Staphylococcus aureus, Enterococcus faecalis using serial dilutions (10⁻¹ to 10⁻³) and CFU analysis. Representative agar plates showed that C-GP significantly reduced biofilm formation, with countable colonies (252 × 10² CFU/mL) at 10⁻³ dilution, while uncoated gutta-percha (U-GP) showed too numerous to count (TNTC) growth at all dilutions. These results demonstrate that SeNPs coating imparts enhanced antibiofilm properties to gutta-percha compared to the conventional form. Conclusion: Selenium nanoparticle coating significantly enhanced the antibiofilm activity of gutta-percha compared to uncoated controls. This surface modification demonstrates promising potential as a novel obturation material to reduce bacterial colonization and improve the success of root canal therapy